2000
DOI: 10.1118/1.598840
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐layer energy filter for realizing conformal irradiation in charged particle therapy

Abstract: A new type of filter for charged particle radiotherapy is developed to reduce unwanted dose transfer to the normal tissues around a tumor. The new filter can make a static irradiation field where the width of the spread-out Bragg peak (SOBP) is two-dimensionally adjusted. That makes the field conformal to the tumor three-dimensionally. The filter is made of many layers produced by using stereolithography. The layer has a miniaturized structure that has geometrical similarity to the conventional ridge filter. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…The problem can be solved by using two regions designed for a narrow and a large spread of the SOBP. 9 Second, condensation of the energy deposition in the narrow SOBP should be compensated by lateral intensity modulation. The compensation is performed by modulation of the irradiation time in this work.…”
Section: Multilayer Filtermentioning
confidence: 99%
See 2 more Smart Citations
“…The problem can be solved by using two regions designed for a narrow and a large spread of the SOBP. 9 Second, condensation of the energy deposition in the narrow SOBP should be compensated by lateral intensity modulation. The compensation is performed by modulation of the irradiation time in this work.…”
Section: Multilayer Filtermentioning
confidence: 99%
“…It was confirmed that the flat top of the peak in the dose distribution could be obtained by this structure. 9 The outer shape of the block is shaved to get a desirable shape for a step-shaped virtual target with 20, 40, and 60 mm thickness as shown in Fig. 2.…”
Section: Multilayer Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…However, since it takes much time for the FMC method to complete the dose calculation in clinical cases, it is difficult at present to apply the FMC calculation to routine clinical treatment planning. To reduce the calculation time, a number of faster Monte Carlo methods dedicated to proton therapy have been developed 10 , 11 , 12 . One of such faster FMC codes for TPS in proton therapy, named VMCpro, was reported to be 35 times faster than the general purpose FMC code GEANT4 for simulations in a phantom with large inhomogeneities (10) .…”
Section: Introductionmentioning
confidence: 99%
“…A simplified Monte Carlo (SMC) method 12 , 13 , 14 , 15 has been developed to obtain dose calculation results more accurately than the PBA in target heterogeneities in a shorter calculation time. It tracks individual proton paths scattered in material and uses a measured depth‐dose distribution in water for dose calculation.…”
Section: Introductionmentioning
confidence: 99%